Simple paired heavy- and light-chain antibody repertoire sequencing using endoplasmic reticulum microsomes - Praneeth Reddy Devulapally; Jörg Bürger; Thorsten Mielke; Zoltán Konthur; Hans Lehrach; Marie-Laure Yaspo; Jörn Glökler; Hans-Jörg Warnatz (Genome Medicine, 2018)
Abstract Existing methods for paired antibody heavy- and light-chain repertoire sequencing rely on specialized equipment and are limited by their commercial availability and high costs. Here, we report a novel simple and cost-effective emulsion-based single-cell paired antibody repertoire sequencing method that employs only basic laboratory equipment. We performed a proof-of-concept using mixed mouse hybridoma cells and we also showed that our method can be used for discovery of novel antigen-specific monoclonal antibodies by sequencing human CD19+ B cell IgM and IgG repertoires isolated from peripheral whole blood before and seven days after Td (Tetanus toxoid/Diphtheria toxoid) booster immunization. We anticipate broad applicability of our method for providing insights into adaptive immune responses associated with various diseases, vaccinations, and cancer immunotherapies.